Consumer behavior theories : convergence of divergent perspectives with applications to marketing and management - Rajagopal (New York, NY : Business Expert Press, 2018)
This book critically examines and analyzes the classical and neoclassical behavioral theories in reference to consumer decision making across the business cultures. The theoretical perspectives of consumer behavior have been explained in the book concerning changing marketplace environment and customer-centric business approaches followed by the multinational companies. The core discussions presented in this book highlight that the new theories can be derived based on the social values, business ambiance, and consumer attitudes to understand the consumer cognitive drivers meticulously and develop synergy with the business strategies. This book is divided into five chapters illustrated with the figures and examples that help readers to easily get the concept and approach of innovative business projects. Discussions in the book presents new insights on drawing contemporary interpretations to the behavioral theories of consumers, and guides the breakthrough strategies in managing the time, territory, target, and tasks pivoting around consumers and market competitiveness. The book illustrates the consumer analysis and market behavior mapping, and guides the companies to build sustainable businesses associating consumers in the competitive marketplace
Keywords: BUSINESS & ECONOMICS Industrial Management; BUSINESS & ECONOMICS Organizational Behavior